Purification and characterization of recombinant enzyme CGTase G1 - Goh, Kian Mau; Mahadi, Nor Muhammad; Hassan, Osman; Raja Abdul Rahman, Raja Noor Zaliha; Md. Illias, Rosli (2005)
The cyclodextrin glucanotransferase (CGTase) gene from Bacillus sp. G1 was successfully isolated and cloned into Escherichia coli. The CGTase gene was expressed in E.coli and approximately 62% of CGTase enzyme was secreted into the medium. The recombinant CGTase was purified to homogeneity using ammonium sulfate precipitation followed by α-cyclodextrin-bound-epoxy-activated Sepharose 6B affinity chromatography. The purified recombinant CGTase exhibited a single band of 75kDa on SDS-PAGE and globular size was determined to be 79kDa by gel filtration chromatography. The enzyme has an optimum temperature of 60°C and optimum pH of 6.0. Phosphate buffer pH 6.0 was found to be more preferred compared to citrate or MES buffer at same pH value. Stability of the recombinant CGTase G1 covered over a wide pH range, from pH 6 to pH 10 where as it has a half-life of 30 minutes at 60°C. Stability and half life was able to be increased by additional of CaCl2.Km and Vmax value for recombinant CGTase from Bacillus sp. Gl was calculated to be 0.468 mgml-1 and 64.1mg β-CD respectively. After 16 hours incubation at 60°C, the yield for cyclodextrin production from tapioca starch as the substrate were 90% for β-cyclodextrin and 10% for α-cyclodextrin without adding any selective agents.